Digital Initiatives at Dhaka University Library - Murshed, S. M. Masum (Cadernos BAD, 2020)
University of Dhaka is the largest and the oldest public university in Bangladesh. The university has more than forty-two thousand students and over two thousand academic staff. The university library1 is the heart of the academic activities on campus serving a big number of students, teachers and researchers. The university library holds about 0.6 million copies of books and about 30 thousand of rare manuscripts, microfilms, microfiche and other records of historical importance. It is the largest library in the country. The library maintains an institutional repository and online archives of digitized contents for the university community and others. The goal of such initiatives is to increase the visibility, use and impact of the university's research publications by offering them to use through the university's own digital archival system. The repository consists of full-text materials produced in the university such as theses, internship reports, journal articles, conference proceedings and research materials produced by all the departments, Institutes, research centers and units of the university. DSpace is used for this repository services. Since June 2012, the repository has been archiving research articles and most importantly all these research publications are of open access allowing university community to have free access to them. Its unique feature is that academic and researchers can also archive their research and other publications in this repository platform. Since this is an open access platform for the university community who can easily get information and relevant research articles from this platform, it is particularly popular among new and young scholars. Additionally, the university library preserves its own digitized newspapers, manuscripts and rare materials in a recently created archival system. This is the first of its kind initiative which has an outstanding impact on access and use of digitized resources in Bangladesh. This poster provides an overview of Dhaka University Library’s institutional repository and archival services currently available. It will also highlight future plans and programs for better library management and services besides increasing access to archival contents for the university community.